Identification of a New Inhibitor That Stabilizes Interleukin-2-Inducible T-Cell Kinase in Its Inactive Conformation. (September 2019) - Hantani, Rie; Hanawa, Saya; Oie, Shohei; Umetani, Kayo; Sato, Toshihiro; Hantani, Yoshiji
Interleukin-2-inducible T-cell kinase (ITK) plays an important role in T-cell signaling and is considered a promising drug target. As the ATP binding sites of protein kinases are highly conserved, the design of selective kinase inhibitors remains a challenge. Targeting inactive kinase conformations can address the issue of kinase inhibitor selectivity. It is important for selectivity considerations to identify compounds that stabilize inactive conformations from the primary screen hits. Here we screened a library of 390, 000 compounds with an ADP-Glo assay using dephosphorylated ITK. After a surface plasmon resonance (SPR) assay was used to filter out promiscuous inhibitors, 105 hits were confirmed. Next, we used a fluorescent biosensor to enable the detection of conformational changes to identify inactive conformation inhibitors. A single-cysteine-substituted ITK mutant was labeled with acrylodan, and fluorescence emission was monitored. Using a fluorescent biosensor assay, we identified 34 inactive conformation inhibitors from SPR hits. Among them, one compound was bound to a site other than the ATP pocket and exhibited excellent selectivity against a kinase panel. Overall, (1) biochemical screening using dephosphorylated kinase, (2) hit confirmation by SPR assay, and (3) fluorescent biosensor assay that can distinguish inactive compounds provide a useful platform and offer opportunities to identify selective kinase inhibitors.